(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. Nitrogen-containing heterocycles are important objects of both fundamental and applied research. They are used in the creation of fine organic synthesis products, pharmaceuticals, agrochemicals, dyes, and more. Functionalized azaheterocycles are promising research targets due to their potential application as efficient building blocks for the synthesis of new heterocyclic derivatives and their broad spectrum of biological activity. Therefore, the search for new approaches and reagents for the construction of such heterocyclic systems is an urgent task. The aim of the present study was to expand the synthetic potential of 2-(2-hetaryl)-2-(tetrahydro-2-furanylidene)acetonitriles for the design of condensed heterocyclic derivatives. Methods. Organic synthesis of new functionalized derivatives based on 2-(4-oxo-3,4-dihydro-2-quinazolinyl)-2-(tetrahydro-2-furanylidene)acetonitriles; structural elucidation and characterization of the synthesized compounds using IR spectroscopy, 1H and 13C NMR spectroscopy, and mass spectrometry. Results. The interaction features of 2-(4-oxo-3,4-dihydro-2-quinazolinyl)-2-(tetrahydro-2-furanylidene)acetonitriles with malononitrile have been established, and the influence of structural factors on the regioselectivity of intramolecular heterocyclizations has been demonstrated. A possibility of forming a mixture of regioisomers – 9-amino-7-(3-hydroxypropyl)-11-oxo-11H-pyrido[2,1-b]quinazoline-6,8-dicarbonitriles and 1-amino-3-(3-hydroxypropyl)-6-oxo-6H-pyrido[1,2-a]quinazoline-2,4-dicarbonitriles, as well as the pathway for their directed transformation into 9-amino-7-(3-hydroxypropyl)-2,4-disubstituted-11-oxo-11H-pyrido[2,1-b]quinazoline-6,8-dicarbonitriles, has been shown. A method has been proposed for the stepwise formation of 2-(6-amino-3,5-dicyano-4-(3-hydroxypropyl)-2-oxopyridin-1(2H)-yl)-N-methylbenzamide and 3-(3-hydroxypropyl)-1,6-dioxo-5,6-dihydro-1H-pyrido[1,2-a]quinazoline-2,4-dicarbonitrile starting from N-substituted furanilideneacetonitrile and malononitrile. Conclusions. Based on the C-nucleophilic modification of 2-(4-oxo-3,4-dihydro-2-quinazolinyl)-2-(tetrahydro-2-furanylidene)acetonitriles, methods for the directed synthesis of 9-amino-7-(3-hydroxypropyl)-2,4-disubstituted-11-oxo-11H-pyrido[2,1-b]quinazoline-6,8-dicarbonitriles, 2-(6-amino-3,5-dicyano-4-(3-hydroxypropyl)-2-oxopyridin-1(2H)-yl)-N-methylbenzamide, and 3-(3-hydroxypropyl)-1,6-dioxo-5,6-dihydro-1H-pyrido[1,2-a]quinazoline-2,4-dicarbonitrile have been developed.